Increase in ventilation caused by aminophylline in the absence of changes in ventral medullary extracellular fluid pH and carbon dioxide tension. Issue 2 (February 1989) - Javaheri, S; Evers, J A; Teppema, L J
Abstract : A study was designed to investigate the possibility that changes in ventral medullary extracellular fluid carbon dioxide tension (PCO2) and hydrogen ion (H+) concentration mediate the ventilatory stimulation induced by systemic administration of aminophylline. Six cats with peripheral chemodenervation (bilateral carotid sinus nerve and vagal neurotomy) were studied while anaesthetised with chloralose urethane and breathing spontaneously at a regulated, constant, and somewhat raised end tidal PCO2. Variables were measured during steady state normoxaemia and 10 and 30 minutes after administration of 17 mg/kg aminophylline (mean (SD) blood concentration of theophylline 14.2 (1.5) mg/l). Aminophylline resulted in a significant and considerable increase in minute ventilation to 155% and 167% above baseline at 10 and 30 minutes. Mean (SD) values for arterial PCO2 were 5.6 (0.6), 5.6 (0.6), and 5.4 (0.6) kPa at 0, 10, and 30 minutes. Values for the ventral medullary extracellular fluid PCO2 were 7.6 (1.1), 7.5 (1.0), and 7.4 (1.0) kPa and for H+ concentration 62.7 (9.3), 62.6 (9.3), and 63.5 (8.0) nmol/l at 0, 10, and 30 minutes. After aminophylline infusion the PCO2 and H+ concentration of the extracellular fluid did not differ significantly from baseline values. It is concluded that in spontaneously breathing, peripherally chemodenervated cats the considerable increase in ventilation that follows an infusion of aminophylline is not mediated by change in the ventral medullary extracellular fluid PCO2 or hydrogen ion concentration.